Street-Level Climate Governance in Pakistan: A Critical Assessment of the Clean and Green Movement (Journal of Contemporary Studies, 2025)
Despite contributing approximately only 1.01% to global greenhouse gas (GHG) emissions, Pakistan remains one of the most vulnerable countries to the impact of climate change. Several environmental initiatives most notably the Clean and Green Pakistan movement, align national efforts with Sustainable Development Goal 13 (Climate Action). This study critically examines the design and implementation challenges of major initiatives including the Ten Billion Tree Tsunami, Recharge Pakistan, and the Clean Green Pakistan Index. Using a qualitative methodology grounded in the analysis of policy documents, government reports, media sources, and institutional data, the research explores how these programs aim to advance environmental sustainability and public awareness. The effectiveness of these programs is constrained by significant implementation barriers, such as inadequate resources, weak intergovernmental coordination, corruption, and limited institutional capacity. These challenges often create a disconnect between national policy ambitions and realities on-ground. Drawing on Michael Lipsky’s Street-Level Bureaucracy framework, the study argues that the success of environmental governance in Pakistan depends not only on sound policy design but also on requires stronger institutional support, enhanced transparency, and more inclusive community engagement to translate environmental commitments into long-term, sustainable outcomes.